1998
DOI: 10.1007/s11357-998-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Pro-oxidant activity of Cu,Zn-superoxide dismutase

Abstract: Whereas Cu,Zn-superoxide dismutase (Cu,Zn-SOD) is an essential antioxidant enzyme for superoxide dismutation in vivo(1 ), many reports have shown that an elevated level of Cu,Zn-SOD induces cell killing (2, 3), increases lipid peroxidation (4,5), and interferes with the transport of neurotransmitters (4, 6). All of these observations are archetypical results inducible by oxygen radicals. Cu,Zn-SOD (7) and FALS mutants (8) are known to develop neurodegeneration. These findings suggest that under certain conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Some investigators believe that AlP mitigates antioxidant defence through the reduction of SOD activity causing cellular toxicity . In contrast, others suppose that AlP increases H 2 O 2 levels via stimulating SOD activity, which is more stable and diffusible than O2, resulting in lipid peroxidation and consequent ROS generation …”
Section: Oxidative Stress: Effect Of Melatonin and Aluminium Phosphidementioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators believe that AlP mitigates antioxidant defence through the reduction of SOD activity causing cellular toxicity . In contrast, others suppose that AlP increases H 2 O 2 levels via stimulating SOD activity, which is more stable and diffusible than O2, resulting in lipid peroxidation and consequent ROS generation …”
Section: Oxidative Stress: Effect Of Melatonin and Aluminium Phosphidementioning
confidence: 99%
“…[4,45,46] In contrast, others suppose that AlP increases H 2 O 2 levels via stimulating SOD activity, which is more stable and diffusible than O ÀÅ 2 , resulting in lipid peroxidation and consequent ROS generation. [47,48] Melatonin can efficiently oppose these events by increasing the activity and expression of ETC complexes leading to ATP production. [49] It is demonstrated that melatonin is a vigorous antioxidant acting as a potent ROS scavenger.…”
Section: Oxidative Stress: Effect Of Melatonin and Aluminium Phosphidementioning
confidence: 99%
“…In another study in insects it was observed that on PH 3 treatment there was a decrease in the activity of catalase and peroxidase with an increase in superoxide dismutase (SOD) activity (Bolter and Chefurka, ), all of them being metalloenzymes. Since PH 3 increases SOD activity, there is dismutation of superoxide anion (O 2 •− ) to produce hydrogen peroxide (H 2 O 2 ), which is more stable and invasive (Yim et al , ). By inhibiting catalase and peroxidase activity, scavenging of peroxide radicals is reduced.…”
Section: Effect At Cellular Levelmentioning
confidence: 99%
“…However, side reactions have been documented (2)(3)(4)(5), and superoxide oxidase and reductase activities, involving in each case only one-half of the copper redox cycle, have recently been reported (6,7). If SOD does have superoxide reductase activity, then thiols are potential biological substrates.…”
mentioning
confidence: 99%